Penerapan Pasca Taman Pendidikan Quran Program Tahfidz dalam Meningkatkan Pembelajaran Tahfidzul Quran Melalui Metode Qira’ati di Era Digital Siswa MI Jam’iyyatul Qurra Tahun Pelajaran 2023/2024 - Sulastri, Siti; Syamsiar, Syamsiar (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2024)
This study aims to analyze the implementation of the Post-Taman Pendidikan Quran (TPQ) Tahfidz Program at MI Jam'iyyatul Qurra for the 2023/2024 academic year, particularly in enhancing Quran memorization learning using the Qira'ati Method. This qualitative research employs a direct approach or field research, including observation, interviews, and documentation. The findings indicate that the program successfully improves students' Quran memorization through key activities such as morning assemblies, Qira'ati and Tahfidz classes, and memorization recitations. To enhance Tahfidz learning in the digital era, the school collaborates with external institutions and motivates students in their Quran memorization. The implementation of the Post-TPQ is carried out to improve the regularity of memorization and discipline among students in using the Qira'ati method and the tahfidz program. Teachers and the school principal play a crucial role in overcoming various challenges. The study concludes that the Qira'ati Method is proven effective in Tahfidz learning, helping students systematically memorize the Quran according to the central Qira'ati guidelines. The principal and Tahfidz teachers acknowledge that while the method significantly supports learning, time challenges persist in meeting the predetermined memorization targets.